CP and CP-PGN protect mice against MRSA infection by inducing M1 macrophages. Issue 1 (December 2017) - Zhang, Yang; Li, Xiang-Xiang; Ma, Yuan; Xu, Jie; Zhao, Li-Na; Qian, Xue-Feng; Zhang, Xian-Feng; Shi, Jin-Fang; Han, Qing-Zhen
Abstract Corynebacterium pyruviciproducens (C. pyruviciproducens, CP), as a newly discovered immunomodulator, has been confirmed to have a stronger immunoregulation thanPropionibacterium acnes (P. acnes ) of the traditional immune adjuvant, by previous experiments with model antigen ovalbumin and sheep red blood cells. Here, it was designed to assess its ability to resist methicillin-resistantStaphylococcus aureus (MRSA), since MRSA as a vital gram positive pathogen is characterized by high morbidity and mortality. In this report, it was indicated thatC. pyruviciproducens and its peptidoglycan (CP-PGN) could help to be against bloodstream infection of MRSA with raised survival rate, decreased bacteria load and alleviated systemic inflammation, and these effects of CP-PGN were more pronounced. However, the whole CP was inclined to prevent localized abdominal infection of MRSA from progressing to a systemic infection. And they showed the potential as a therapeutic drug alone or combined with vancomycin. The diversity of capacity of activating macrophages induced by CP and CP-PGN may result in distinct resistance to MRSA in different infection models. Furthermore, both CP and CP-PGN induced M1 macrophages. In conclusion, CP and its PGN could act as promising immune agents to treat and prevent MRSA infection.